SOCIO-ECONOMIC CONDITIONS LABOR FISH AUCTION (TPI) AIR BANGIS SUNGAI BEREMAS DISTRICT PASAMAN BARAT REGION - PANGIDOAN, ELISA; Juita, S.Pd. M.Si, Erna; Prari Keslan, Widya (Pendidikan Geografi, 2014)
ABSTRACT This study aimed to obtain the data, process, and an overview of the Socio-Economic Conditions Labor Fish Auction (TPI) Air Bangis Sungai Beremas District Pasaman Barat Region, viewed from: 1) The level of income , 2) Level of Education, 3) Soundness, 4) Work Ethic and 5) Social InteractionThis research is descriptive. Population was Labor In Fish Auction (TPI) Air Bangis Beremas District Pasaman Barat Region totaling 104 workers. Samples were taken entirely by total sampling technique.The results showed: 1) The level of labor income by Achievement Level Respondents (TCR) are in kind enough position with the percentage (74,8%) viewed from the labor income: non-food expenditure of labor/ year is Rp  1.500.000 - Rp 2.500.000 and expenses, food expenses / month Rp 600.000 - Rp  800.000/month and expenditures for childrens education costs Rp 500,000 - Rp  600.000/month, then from the above description can be concluded that the amount of revenue is Rp 1.225.000 - Rp . 1.400.000/month, when compared with the regional minimum wage (UMR) Pasaman Barat Rp 1.350.000/month including middle- income, 2) The level of education of workers by Achievement Level Respondents (TCR) are in kind enough position with the percentage (76,3%), 3) the level of health of workers by level of achievement Respondents (TCR) are in kind enough position with the percentage (72,9%), 4) work ethic of a worker by achievement Level Respondents (TCR) are in a position unfavorable to the percentage (61,8%), and 5) social interaction based achievement Level Respondents (TCR) are in fairly good position with a percentage ( 69,4%).